The Chancellor's Spiritual Leadership in Increasing Work Motivation of Lecturers and Employees - Moh. Harun Al Rosid; Titiek Rohanah Hidayati; Moh. Anwar (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
The aims of this research are (1) to describe the rector's spiritual leadership and (2) to describe the motivation of university lecturers and employees. This research approach is qualitative while the type is a case study. Research location at KH University. Mukhtar Syafa'at (UIMSYA) Blokagung Banyuwangi. Researchers as key instruments. The research subjects were the rector, lecturers and staff. Determining informants using purposive sampling. Data collection techniques are observation, interviews and documentation. The data analysis is an interactive model of Miles, Huberman and Saldana theory of data condensation, data presentation, and drawing conclusions. Test the validity of the data using credibility, dependability and confirmability tests. Data validity is checked through continuous, triangulation, member checking, peer discussion, and reference checking. The results of the research are (1) The spiritual leadership of the university rector emulates the Prophet Muhammad SAW, achieves the organizational vision with his subordinates, integrates Islamic boarding school values into the Tridharma, builds a social culture of work with love and altruism, establishes cooperation with the Banyuwangi government. (2) The chancellor's motivation for university lecturers and employees is intrinsic; appreciate the struggle of the founder of the Islamic boarding school, integration of Islamic boarding school values, the culture of reading the Koran, istighosah, and praying. Extrinsic; promotion to positions of outstanding lecturers and employees, scholarship incentives of 50% of tuition fees, professional development, periodic salary increases, and sanctions for those who do not comply with regulations.